Involvement of phenolic compounds and their composition in the defense response of Fusarium oxysporum infected berangan banana plants - Fung, Shi Ming; Zuliana Razali; Chandran Somasundram (Penerbit Universiti Kebangsaan Malaysia, 2021)
Fusarium wilt is one of the most common destructive banana diseases which causes great losses to the global banana production. Berangan banana, known to be very susceptible towards this disease is greatly affected. Upon infection, oxidative burst involving rapid accumulation of reactive oxygen species is one of the first responses of a plant defense against biotic and abiotic stress. Secondary metabolites play an essential role in scavenging these toxic reactive radicals. In this study, a number of phenolic compounds and flavonoids were identified and the changes were documented. Compounds such as quinic acid, ferulic acid, caffeoyl glucose, p-coumaric acid, syringic acid, sinapic acid, aconitic acid, caffeic acid, p-hydroxybenzoic acid, ascorbic acid, kaempferol-rhamnose-hexose, quercetin, catechin, rutin, and isorhamnetin 3-O rutinoside increased after fungal infection. Concomitantly, DPPH radical scavenging activity, reducing power, total antioxidant activity, total flavonoid content and total polyphenol content also increased. Polyphenols, flavonoid content and antioxidant activities increased significantly on day 1 and continued to increase until day 6 before gradually declining. The phenolic and flavonoid profiles were analysed using liquid chromatography - mass spectroscopy (LCMS). The antioxidant properties were found to be closely related to plant defense system.